Superelectrophilicity in Michael-Type Reactions: Water Addition to 4-Nitrobenzodifuroxan - Lakhdar, Sami; Berionni, Guillaume; Terrier, François (Synthesis, 2017)
Kinetic and thermodynamic measurements of the ease of covalent hydration of 4-nitrobenzodifuroxan (NBDF) to give the corresponding hydroxy adduct has been carried out over a large pH range of 0.82–12.23 in aqueous solution. A most important result is that water is the sole efficient nucleophile contributing to the hydration of this peculiar nitroolefin in the pH range 4–8. Based on this finding as well as a pKaH2O value of 2.85 for the complexation process there is no doubt that the electrophilic character of NBDF falls in the domain of superelectrophilicity defined with reference to covalent nucleophilic additions to 4,6-dinitrobenzofuroxan (DNBF; pKaH2O = 3.75) and related heterocycles. This also corresponds to a positioning of NBDF at the top of the electrophilicity scale E introduced by Mayr to describe the feasibility of nucleophilic-electrophilic combinations. Returning to the hydration of the series of activated olefins, it has been possible to expand the domain of reactivity of Michael acceptors by six orders of magnitude, going from benzylidenemalonitrile (pKaH2O = 10.70; E = –9.42) to the para-nitro-substituted benzylidene Meldrum’ s acid (pKaH2O = 3.46; E = –5.49). The positioning of these olefins on the pKa scale shows that not only 4-nitrobenzodifuroxan but also the unsubstituted Meldrum’s acid are located in the superelectrophilic region.
Keywords: superelectrophiles; Michael additions; nitroolefins; covalent hydration; electrophilicity scales; kinetics